Respuesta a la aplicación de cinco dosis de roca fosfórica y humus de lombriz en el cultivo de repollo (brassica oleracea l. var. capitata) en suelos ácidos del fundo Aucaloma de la Unsm – Lamas - Sandoval Suclupe, Rosa Mili (2012)
This research paper entitled "Response to the application of five doses of phosphate rock and humus in the cultivation of cabbage(Brassicaoleracea L.) In acid soils of the farm aucaloma UNSM-Lamas", aimed to assess the phenological responses, morphological and crop yield of cabbage (Brassica oleracea L.) variety ox heart, regarding the application of phosphate rock in acid soils, with the place of performance of the Fundo Aucaloma National University of San Martin-Tarapoto, located in the hamlet of Aucaloma 15 km from Tarapoto, in the district of San Roque de Cumbaza, Lamas province and region of San Martin, which was used to design a randomized complete block (RCBD), which consisted for 4 blocks and 7 treatments, being distributed by T1 (control), T2 (4000 kg/ ha of humus), T3(500 kg/ ha RF+ 4000 kg/ ha of humus), T4 (1000kg / ha RF + 4000 kg/ ha of Humus) , T5 (1500 kg / ha RF+ 4000 kg/ ha of Humus), T6 (2000 kg / ha RF + 4000 kg / ha of Humus) and T7 (2500 kg/ ha + 4000 RF kg /has Humus) The most important conclusions were the T5 (1500 kg/ ha of R.F+4000 kg/ha /humus) showed higher plant height of 31.63 cm, with the largest number of leaves reaching the plants during the growing period of the crop was the T5 (1500 kg/ ha of RF + 4000kg/ha /humus) and T4 (1000 kg/ ha RF + 4000 kg/ha /humus) with 13.25 and 12.85 respectively leaves on average, with the largest diameter heads were hit by the treatments T5 (1500kg/ ha of RF+ 4000 kg/ha /humus), T7(2500 kg/ ha of RF+ 4000 kg /ha /humus), T6 (2000 kg/ ha of RF + 4000 kg/ha /humus) and T3 (50kg/ ha of RF + 4000 kg/ha /humus) with 34.45, 33.70, 33.48 and 32.55 cm respectively, the highest yield was obtained by the T7(2500 kg / ha of RF + 4000 kg/ ha of Humus) with 18.63 t/ ha.